2021
DOI: 10.1109/tro.2021.3075644
|View full text |Cite
|
Sign up to set email alerts
|

ORB-SLAM3: An Accurate Open-Source Library for Visual, Visual–Inertial, and Multimap SLAM

Abstract: This article presents ORB-SLAM3, the first system able to perform visual, visual-inertial and multimap SLAM with monocular, stereo and RGB-D cameras, using pin-hole and fisheye lens models. The first main novelty is a tightly integrated visualinertial SLAM system that fully relies on maximum a posteriori (MAP) estimation, even during IMU initialization, resulting in real-time robust operation in small and large, indoor and outdoor environments, being two to ten times more accurate than previous approaches. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
754
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,968 publications
(1,034 citation statements)
references
References 68 publications
3
754
0
2
Order By: Relevance
“…Another problem that must be considered is occlusion. In static cases, the quality of 3D landmarks is defined by the number of observations [7,21]. Landmarks occluded by a slowly moving object may be culled because of a lack of observations.…”
Section: Robust Slammentioning
confidence: 99%
See 1 more Smart Citation
“…Another problem that must be considered is occlusion. In static cases, the quality of 3D landmarks is defined by the number of observations [7,21]. Landmarks occluded by a slowly moving object may be culled because of a lack of observations.…”
Section: Robust Slammentioning
confidence: 99%
“…In contrast, the latter selects only a small number of past frames and applies bundle adjustment (BA) to those frames [3]. Although many frame-based SLAM methods [4][5][6][7] have demonstrated that the BA method is more efficient for V-SLAM, filtering methods are still worth studying for dynamic SLAM based on their natural advantages in terms of handling statistical information, which is important for depth estimation [8], sensor fusion [9], dynamic feature determination [10], and robust map management [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In order to directly demonstrate the results of loop closure detection methods, SVG-Loop was transplanted to ORB-SLAM3 [13], which is one of the most popular visual SLAM systems. Keyframes of the front-end visual odometer were used as input for the SVG-Loop model.…”
Section: Indoor Datasetmentioning
confidence: 99%
“…Then, the trajectory graph of different methods was used to visually display the loop closure detection results. Two monocular visual SLAM systems, LDSO [54] and ORB-SLAM3 [13], that include loop closure detection modules were selected to complete comparative experiments with ORB-SLAM3 + SVG-Loop. Furthermore, trajectory error was computed to evaluate the impact of the SVG-Loop algorithm on SLAM system accuracy.…”
Section: Indoor Datasetmentioning
confidence: 99%
See 1 more Smart Citation